Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1136/bmj.312.7039.1121
|View full text |Cite
|
Sign up to set email alerts
|

Has mortality from melanoma stopped rising in Australia? Analysis of trends between 1931 and 1994

Abstract: Melanoma mortality in Australia peaked in about 1985 and has now plateaued. On the basis of trends in cohorts it can be expected to fall in coming years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
120
0
13

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(138 citation statements)
references
References 25 publications
(36 reference statements)
5
120
0
13
Order By: Relevance
“…The medical literature indicates that these did not start at the same time in all countries: in some Australian states, prevention programmes started in the 1960s (Giles et al, 1996) and then national programmes ('Slip, Slop, Slap' and 'Sun Smart') followed in the 1980s. In the USA, Canada, UK and Sweden, national programmes started in the 1980s or early 1990s (Robinson et al, 1997; Rivers and Gallagher, 1995;Melia, 1995;Möller et al, 1997).…”
Section: Is the End Of The Increasing Trend In Sight?mentioning
confidence: 99%
See 1 more Smart Citation
“…The medical literature indicates that these did not start at the same time in all countries: in some Australian states, prevention programmes started in the 1960s (Giles et al, 1996) and then national programmes ('Slip, Slop, Slap' and 'Sun Smart') followed in the 1980s. In the USA, Canada, UK and Sweden, national programmes started in the 1980s or early 1990s (Robinson et al, 1997; Rivers and Gallagher, 1995;Melia, 1995;Möller et al, 1997).…”
Section: Is the End Of The Increasing Trend In Sight?mentioning
confidence: 99%
“…There is also evidence that CMM mortality rates are plateauing or beginning to fall in recent generations in the USA and in Australia (Scotto et al, 1991;Rousch et al, 1992;Giles et al, 1996). These declines in mortality are, however, restricted to recent birth cohorts while death rates continue to increase in older generations.…”
mentioning
confidence: 99%
“…Introduction of the Papanicolaou test in the 1950s was followed by a dramatic decline in cervical cancer in those countries that made widespread screening available (Laara et al, 1987). The decline in Australian melanoma mortality for those born after 1950 is an additional example of effective intervention at the population level (Giles et al, 1996).…”
mentioning
confidence: 99%
“…It is impossible to claim an effect from one specific factor although early detection may well have contributed. In Australia (Giles et al, 1996) a greater reduction in melanoma mortality was observed following an intensive early detection intervention in Queensland in the 1960s than in other states.…”
Section: Effects Of Early Detection On Melanoma Mortality 805mentioning
confidence: 99%
“…Mortality from melanoma has been falling or reaching a plateau in several countries (Streetly and Markowe, 1995;Giles et al, 1996;MacKie et al, 1997;La Vecchia et al, 1999;CohnCedermark et al, 2000;Severi et al, 2000). In the UK these trends first seemed to start before the interventions in 1985and 1987(Streetly and Markowe, 1995MacKie et al, 1997).…”
Section: Effects Of Early Detection On Melanoma Mortality 805mentioning
confidence: 99%